Longitudinal Study of Self-efficacy and Personal Growth Initiative in Argentine Secondary School Students - Schönfeld, Fátima Soledad (2025)
Objective. This study aimed to: a) analyze the trajectory of self-efficacy in Argentine secondary school students over three consecutive years, and b) examine its association with the personal growth initiative (PGI) at each measurement. Method. This longitudinal study included 313 students at T1, 280 at T2, and 249 at T3. Argentine adaptations of the O'Sullivan Self-Efficacy and PGI-II scales were applied. Repeated Measures ANOVA was used to study the trajectory of self-efficacy, and Pearson's r correlation was used to analyze the associations. Results. Self-efficacy showed a decrease towards the third time point. Positive and significant correlations were observed between all self-efficacy dimensions and PGI.